2021
DOI: 10.1016/j.jtbi.2020.110514
|View full text |Cite
|
Sign up to set email alerts
|

Combining refuges with transgenic insect releases for the management of an insect pest with non-recessive resistance to Bt crops in agricultural landscapes

Abstract: Reinforcing the high-dose/refuge strategy with releases of transgenic insects has been posited as a method for simultaneously managing agricultural pest populations and resistance to transgenic crops. Theoretical and empirical studies have shown that these approaches can work when deployed against closed populations and the assumptions of the HDR strategy are met. However, field-evolved resistance is often linked to non-recessive resistance or refuge non-compliance, and pest management regimes are likely to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…If approved for cultivation, this Bt maize could be grown in rotation with maize MON 810 enabling the alternation of Bt proteins with a different mode of action, thus avoiding repeated selection pressure encountered in continuous maize MON 810 cultivation, as is often practiced in Spain [71]. Additional approaches, such as combining the HDR strategy with mass releases of sterile insects [124] or male GE insects with a female-specific self-limiting gene [125,126] have been proposed or applied for simultaneously managing agricultural insect pest populations and resistance to Bt crops. In the southwestern United States and northern Mexico, for instance, the combined use of Bt cotton and mass release of sterile pink bollworm (Pectinophora gossypiella) moths has enabled the successful suppression of this invasive pest [124] and the replacement of refuges with mass releases of sterile insects.…”
Section: Discussionmentioning
confidence: 99%
“…If approved for cultivation, this Bt maize could be grown in rotation with maize MON 810 enabling the alternation of Bt proteins with a different mode of action, thus avoiding repeated selection pressure encountered in continuous maize MON 810 cultivation, as is often practiced in Spain [71]. Additional approaches, such as combining the HDR strategy with mass releases of sterile insects [124] or male GE insects with a female-specific self-limiting gene [125,126] have been proposed or applied for simultaneously managing agricultural insect pest populations and resistance to Bt crops. In the southwestern United States and northern Mexico, for instance, the combined use of Bt cotton and mass release of sterile pink bollworm (Pectinophora gossypiella) moths has enabled the successful suppression of this invasive pest [124] and the replacement of refuges with mass releases of sterile insects.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Cardano formula, the above one-dimensional cubic Equation (13) can be equated to (m…”
Section: Flip Bifurcation Analysismentioning
confidence: 99%
“…The dynamics of insect populations are not only influenced by various abiotic factors, such as temperature [ 5 , 6 ], altitude [ 7 ], and humidity [ 8 ], but also largely mediated by predator–prey interactions [ 9 , 10 ]. Refuge effects, a vital influence factor in the insect predator–prey systems [ 11 , 12 , 13 ], provides a degree of protection for insect populations from predation [ 11 , 14 , 15 ]. Such spatiotemporally discrete systems are complex, sensitive and prone to chaos [ 16 , 17 , 18 , 19 ], whose fluctuations in species abundance or growth rate tend to occur simultaneously across spatial sites [ 20 , 21 ], leading to elusive spatial and temporal dynamics [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Previous studies found that target insects such as Helicoverpa armigera, Helicoverpa zea, and P. xylostella have evolved resistance to Bt-transgenic crops. [6][7][8][9] 9 Plutella xylostella has exhibited high-level resistance to Bt biotoxins sprayed in the field. 10 Hence, it is urgent to develop strategies that can delay the resistance of target insect to Bt-transgenic plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that target insects such as Helicoverpa armigera , Helicoverpa zea , and P . xylostella have evolved resistance to Bt‐transgenic crops 6–9 . Plutella xylostella has exhibited high‐level resistance to Bt biotoxins sprayed in the field 10 .…”
Section: Introductionmentioning
confidence: 99%